Alumni opportunities using machine learning - Siaum, Arshif Sharlimin; Amin, Md. Jawad; Islam, Kamrul (BRAC University, 2019)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.